2022
DOI: 10.3389/fvets.2022.986739
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of mortality in domesticated ruminants in Ethiopia

Abstract: BackgroundPremature death of livestock is a problem in all ruminant production systems. While the number of premature ruminant deaths in a country is a reasonable indicator for the nation's health, few data sources exist in a country like Ethiopia that can be used to generate valid estimates. The present study aimed to establish if three different data sets, each with imperfect information on ruminant mortality, including abortions, could be combined into improved estimates of nationwide mortality in Ethiopia.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…Despite the large population of goats (30.20 million) in Ethiopia ( CSA, 2016 ), the economic benefits of livestock are restricted due to diseases, malnutrition, inadequate management, and lack of access to veterinary care, despite being an abundant resource. This contributes to high morbidity and mortality rates, with annual losses of up to 50% of the total livestock product value ( Innocent et al, 2022 ). Goats frequently contract gastrointestinal (GI) parasitic infections, particularly nematodes, which result in significant economic losses due to animal mortality and decreased weight gain ( Dey et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Despite the large population of goats (30.20 million) in Ethiopia ( CSA, 2016 ), the economic benefits of livestock are restricted due to diseases, malnutrition, inadequate management, and lack of access to veterinary care, despite being an abundant resource. This contributes to high morbidity and mortality rates, with annual losses of up to 50% of the total livestock product value ( Innocent et al, 2022 ). Goats frequently contract gastrointestinal (GI) parasitic infections, particularly nematodes, which result in significant economic losses due to animal mortality and decreased weight gain ( Dey et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…A. Data Management Framework After carefully reviewing research publications, we identified limitations in the current science of art [8,[12][13][14][15][16][17], and through discussions with key stakeholders, we explored their roles and proposed the following ELHRs, as shown in FIGURE 1. The diverse data values related to different stakeholders with detailed descriptions is also presented in TABLE 1.…”
Section: Methodsmentioning
confidence: 99%
“…Outbreak and Vaccination Reporting System (DOVAR) is a digital platform to manage and report disease outbreaks. Its main purpose is to conduct national passive surveillance through the collection of animal disease outbreaks and vaccination data on a monthly basis [14]. Nevertheless, this platform proves effective for managing livestock health data, it lacks the comprehensiveness and functionalities to address the entire range of livestock health-related information and beside it failed to provide timely livestock health-related information.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…On these grounds, disease-associated livestock morbidity and mortality have become a highly relevant topic for international policy and research in Ethiopia, and a considerable number of research initiatives have been generated over recent years, resulting in an increasing volume of evidence. However, the evidence suggests that mortality rates are variable, and that disease causing deaths can vary greatly over geography and time ( 9 ). Although, there have been some comprehensive efforts to collate evidence for specific ruminant diseases in the country, no systematic mapping of the whole body of evidence has so far been undertaken.…”
Section: Introductionmentioning
confidence: 99%